Application of biochar in mitigation of negative effects of salinity stress in wheat (Triticum aestivum L.). (25th February 2018) - Kanwal, Sidra; Ilyas, Noshin; Shabir, Sumera; Saeed, Maimona; Gul, Robina; Zahoor, Maryum; Batool, Nazima; Mazhar, Roomina
ABSTRACT: Salinity is a major abiotic stress that affects crop production throughout the world. Biochar is an activated carbon soil conditioner that can alleviate the negative impacts of salinity. The research was conducted to evaluate the ameliorative effect of 1% and 2% of biochar application on wheat seed germination and growth attributes under salinity. Both levels of biochar improved the germination and growth conditions under salinity; however, 2% biochar level was more effective compared to 1% level. Root and shoot length increased up to 23% and11% with 2% biochar, respectively. The maximum increase of 16% and 10% in leaf water potential and osmotic potential was noted with 2% biochar at 150 mM salt. The decrease in proline content and soluble sugar at 2% biochar was 51% and 27%, respectively. Decrease in superoxide dismutase activity was 15.3% at 2% level of biochar under stress biochar mitigates the negative effects of salinity and improved wheat productivity.